The Influence of Service Quality on Iranian Students Satisfaction, Loyalty and Word of Mouth Communication in Eastern Mediterranean University in Northern Cyprus - Nia, Naser Elahi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
In the current competition in the academic world, students have different options to choose from.Thus, the factors that help institutions in higher education to appeal to and enrol new students should be earnestly examined. Institutions in higher education, seeking competitive advantage, may have to initiate the quest for real and innovative means to appeal to, keep and nurture robust relations with their students. This study’s objective is to investigate the effect of service quality (SERVQUAL) on the satisfaction of the students and behaviors post-satisfaction i.e. loyalty and word of mouth (WOM) communıcatıon. Furthermore, investigating the intervening role of loyalty in the relationship between satisfaction and WOM among Iranian students. For this purpose, 324 Iranian students at Eastern Mediterranean University in Northern Cyprus were chosen to participate in the study. Sample was drawn from almost all faculties. IBM Spss 22 was used in examining the relationships. The findings highlighted that the dimensions of service quality are significantly related with satisfaction, likewise loyalty and WOM. Also, the relationship between loyalty and WOM was proven. The study examined a conceptual model that tested customer satisfaction and its subsequent behaviors (loyalty and WOM) with service quality. Research was conducted among Iranian students from different faculties and degree programs. The results of this study depicted all sevice quality dimensions have relationship with satisfaction and its subsequent behaviors. Keywords: Loyalty, Student Satisfaction, Service Quality, Higher Education and Word of mouth communication.

ÖZ: Akademik dünyadaki mevcut yarışmada, öğrencilerin seçebilecekleri farklı seçenekler bulunmaktadır. Bu nedenle, yüksek öğrenim kurumlarına yeni öğrencilere başvuruda bulunmaları ve yeni öğrencilere kaydolmaları için yardımcı olan etmenler titizlikle incelenmelidir. Rekabet üstünlüğü arayışında olan yüksek öğrenim kurumları, öğrencilerle sağlam ilişkilere sahip çıkmak, onları korumak ve beslemek için gerçek ve yenilikçi araçlar arayışını başlatmak zorunda kalabilir. Bu çalışmanın amacı, hizmet kalitesinin, öğrencilerin tatmin ve tatmin edici davranışları, yani sadakat ve ağızdan ağıza iletişim üzerindeki etkisini araştırmaktır. Ayrıca, İranlı öğrenciler arasında memnuniyet ve ağızdan ağıza iletişim arasındaki ilişkide sadakatin rolünü araştırmaktadır. Bu amaçla Kuzey Kıbrıs'taki Doğu Akdeniz Üniversitesi'ndeki 324 İranlı öğrenci çalışmaya katılmıştır. Örnek neredeyse tüm fakültelerden alınmıştır. İlişkiler SPSS İstatistik 22 kullanılarak test edildi. Sonuçlar, hizmet kalitesi boyutlarının memnuniyet, aynı şekilde sadakat ve ağızdan ağıza iletişim ile anlamlı bir ilişkisi olduğunu gösterdi. Ayrıca, sadakat ve ağızdan ağıza iletişim arasındaki ilişki kanıtlandı. Çalışmada, müşteri memnuniyetini ve daha sonraki davranışlarını hizmet kalitesi ile test eden kavramsal bir model incelendi. Araştırma, farklı fakülte ve yüksek lisans programlarından gelen İranlı öğrenciler arasında yürütülmüştür. Bu çalışmanın sonuçları, tüm servis kalite boyutlarının, memnuniyet ve sonraki davranışlarıyla ilişkisini göstermektedir. Çalışma yöneticiler için iyi tanımlanmış sonuçlar sunmakta, çalışmanın sınırlamaları hakkında bilgi vermekte ve gelecekteki araştırmalar için önerilerde bulunmaktadır. Anahtar Kelimeler: Sadakat, Öğrenci Memnuniyeti, Hizmet Kalitesi, Yüksek Öğrenim ve Ağız İfadesi.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2018. Supervisor: Assoc. Prof. Dr. A. Tarık Timur.
Keywords: Business Administration; Marketing Management; Student Satisfaction-- --Eastern Mediterranean University--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Student Satisfaction--Evaluation; Loyalty; Student Satisfaction; Service Quality; Higher Education and Word of mouth communication